Niewykonalne wyzwanie? Ogólnopaństwowa baza danych zbiorów muzealnych: doświadczenie Białorusi, Rosji, Ukrainy oraz Polski. - Riabchykova, Faina D.; Рябчикова, Фаїна Денисівна (Muzeum Lubelskie w Lublinie, 2019)
The article presents the topics surrounding the creation of state-wide databases of museum collections in Belarus, Russia, Ukraine and Poland. In the postSoviet states, the idea of generating an assembly of information about all the museum objects was formed during the times of the USSR. In the 2nd half of the 1960s, a decision was made to create the Joint Scientific Catalogue of the Museum Resource of the USSR. It was impossible to fulfil the task then, due to the lack of developed substantive bases. After 1991, the newly-formed states created their own bases of museology independently, including the topics of state-wide museum databases. In 2005 in the Republic of Belarus, the State Catalogue of the Museum Resource of the Republic of Belarus was established. The database contains news about particularly valuable museum objects. The State Catalogue of Museum Resources of the Russian Federation was founded in 1996. The information system includes the register of Museum Resource (all museum objects and collections), the register of museums, the register of transactions with museum objects and collections. After the fall of the USSR, Ukraine did not continue to create a state-wide catalogue of the museum objects. After losing a part of its museum collections (in Crimea and the eastern territories of Luhansk and Donetsk Oblasts), the inventory books were copied. After 2014, actions were taken in Ukraine to improve the rules for keeping records of museum collections; at the central level a declaration was made to create a state-wide electronic information resource with databases about cultural heritage objects (including objects from the Museum Resources of Ukraine). In Poland, the first initiatives to create a state-wide database of museum objects were made in the mid-1990s. They had a bottom-up character and did not receive financial support. Polish museums are working on projects of digitalisation of museum collections, a large part of which is financed by the Ministry of Culture and National Heritage. On various levels in the country, the postulates are still formed about the necessity to create a state-wide database, repository and museum resources portal.
Unaccomplishable challenge? State-wide database of museum collections: experience of Belarus, Russia, Ukraine and Poland
Keywords: museum; museum objects; museum collections; database; repository; electronic inventory; digitalisation; National Museum Resource